2014
DOI: 10.2478/biorc-2014-0026
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Lady’s slipper orchid (Cypripedium calceolus L.) population at Lake Kwiecko (West Pomerania)

Abstract: Cypripedium calceolus is considered an endangered species in the territory of Poland. Population of this rare species, situated at Lake Kwiecko (Western Pomerania), was regularly monitored in the years 1986-2013. The studied population has been under the permanent influence of the nearby hydroelectric power plant for almost 45 years. The field observations showed that the power plant had no negative impact on the condition of Cypripedium calceolus population. An indication of its good condition was, among othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Korczyński & KrasickaKorczyńska (2014) found that "in 2013, out of 24 blooming stems 8 fruits were set" in the population near the Lake Kwiecko, without indicating of flowers number at blooming stems. However, the fruit set shown in MR population (36.7% as a mean over study period) was higher than, for instance, in Estonia (Kull 1998), Sweden (Nilsson 1979), the Moscow region of Russia (Varlygina & Matsenko 1986), Buzuluksky Bor National Park (Stetsuk 2013) and Lake Kwiecko in West Pomerania (Korczyński & Krasicka-Korczyńska 2014). The values of fruit set are comparable only with data from Belorussia (Stavrovskaya 1984).…”
supporting
confidence: 56%
See 1 more Smart Citation
“…Korczyński & KrasickaKorczyńska (2014) found that "in 2013, out of 24 blooming stems 8 fruits were set" in the population near the Lake Kwiecko, without indicating of flowers number at blooming stems. However, the fruit set shown in MR population (36.7% as a mean over study period) was higher than, for instance, in Estonia (Kull 1998), Sweden (Nilsson 1979), the Moscow region of Russia (Varlygina & Matsenko 1986), Buzuluksky Bor National Park (Stetsuk 2013) and Lake Kwiecko in West Pomerania (Korczyński & Krasicka-Korczyńska 2014). The values of fruit set are comparable only with data from Belorussia (Stavrovskaya 1984).…”
supporting
confidence: 56%
“…In different regions of Eurasia, C. calceolus has been estimated as Near Threatened (Bilz 2011, Turis et al 2014, Vulnerable (Rassi et al 2001), Endangered (Witkowski et al 2003), and Critically Endangered (Blinova & Uotila 2011, Khapugin et al 2017a, Khapugin et al 2017c. International studies on C. calceolus related to its genetic diversity (Brzosko et al 2009, Brzosko et al 2011, Fay et al 2009, Kļaviņa et al 2014, Minasiewicz & Znaniecka 2014, population ecology and biology (Blinova 2002, Brzosko 2002, Davison et al 2013, Fardeeva et al 2010, Gajewski & Marcisz 2014, Khapugin et al 2014, Korczyński & Krasicka-Korczyńska 2014, García et al 2002, García et al 2010, Gorchakovskii & Igosheva 2003, Kirillova 2015, Kull 1998, Nicolè et al 2005, Puchnina 2017, Stetsuk 2013, Zheleznaya 2015, impacts of environment conditions and stress-factors on the species (Blinova 2002, Czerepko et al 2014, Kirillova 2016, Kirillova et al 2012, Puchnina 2017, Shefferson et al 2012, pollination (Antonelli et al 2009, Tremblay 1994, as well as the list of publications with new records of this threatened species is continuously enlarging ...…”
mentioning
confidence: 99%
“…The analyzed Humic Technosol did not show features of gleyic processes, however, the location conditions (vicinity of the lake) certainly influence the water infiltration at deeper levels and determine the more humid microclimate. A thorough analysis of the development conditions and the dynamics of changes in the lady's-slipper orchid population in the Kwiecko Lake area (Korczyński and Krasicka-Korczyńska, 2014) shows that in recent decades the lady's-slipper orchid population occupies an area that is located about 1 m above the lake level. The current water level in the lake was raised by 3.1 m in 1971 after the construction of a hydroelectric power plant.…”
Section: Discussionmentioning
confidence: 99%
“…The study determined the habitat conditions in which the population of lady's-slipper orchid (Cypripedium calceolus), rare in this area, developed. According to the study by Korczyński and Krasicka-Korczyńska (2014), the population size in this area was 150-350 specimens. In the middle of the patch, a soil pit was dug, in which numerous artifacts in the form of brick rubble and enamel were found, which testify to the anthropogenic material from which the studied soil developed.…”
Section: Methodsmentioning
confidence: 99%